Reducing Attendance Problems in the Group Treatment of Test Anxiety - Grassick, Patrick (Canadian Journal of Counselling and Psychotherapy, 2011)
In university and college counselling services, attendance problems in group programs may lead to poorly informed attempts to modify the programs and can provoke uninformed speculation about treatment effectiveness, as well as producing other difficulties. In spite of their importance, attendance issues have attracted little attention in counseling literature. Studies on the group treatment of test anxiety, on the other hand, have dealt with this subject in a limited way. Some authors have speculated that attendance problems may be rooted in the characteristics of students who drop out, while others have reported on the uncontrolled use of incentives to promote attendance. Data collected over thirteen years in a test anxiety treatment program (N = 736) demonstrate that shortening the program and instituting a 5 deposit significantly reduce attendance problems, suggesting that such factors may be the critical factors influencing attendance variables.